2017
DOI: 10.1161/jaha.117.005790
|View full text |Cite
|
Sign up to set email alerts
|

Potent Vasoconstrictor Kisspeptin‐10 Induces Atherosclerotic Plaque Progression and Instability: Reversal by its Receptor GPR54 Antagonist

Abstract: BackgroundKisspeptin‐10 (KP‐10), a potent vasoconstrictor and inhibitor of angiogenesis, and its receptor, GPR54, have currently received much attention in relation to pre‐eclampsia. However, it still remains unknown whether KP‐10 could affect atherogenesis.Methods and ResultsWe evaluated the effects of KP‐10 on human umbilical vein endothelial cells, human monocyte‐derived macrophages, human aortic smooth muscle cells in vitro, and atherosclerotic lesions in apolipoprotein E–deficient (ApoE−/−) mice in vivo. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
75
2
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(79 citation statements)
references
References 45 publications
0
75
2
6
Order By: Relevance
“…In human aortic smooth muscle cells, KP-10 significantly suppressed angiotensin II-induced migration and proliferation, but increased apoptosis and the activities of MMP-2 and MMP-9 via the upregulation of extracellular signal-regulated kinase 1 and 2, p38, Bax, and caspase-3. MMP-2 increases cancer cell migration by degrading extracellular collagen tissue (39).…”
Section: Discussionmentioning
confidence: 99%
“…In human aortic smooth muscle cells, KP-10 significantly suppressed angiotensin II-induced migration and proliferation, but increased apoptosis and the activities of MMP-2 and MMP-9 via the upregulation of extracellular signal-regulated kinase 1 and 2, p38, Bax, and caspase-3. MMP-2 increases cancer cell migration by degrading extracellular collagen tissue (39).…”
Section: Discussionmentioning
confidence: 99%
“…However, anatomic considerations preclude this as a likely explanation for the aforementioned observations in the aorta and superior mesenteric artery and for arterioles not arranged in parallel with venules. A third possibility is release of inflammatory mediators the produce hyperreactive vasoconstrictor responses that limit NO-dependent dilation in arterial vessels, as has been observed in atherosclerotic plaques (Sato, Shirai, Hontani, Shinooka, Hasegawa, Kichise, et al, 2017). Similar responses have been suggested to play a role in vascular smooth muscle hyperreactivity associated with variant angina (Lanza & Maseri, 2000).…”
Section: Leca In Postcapillary Venules Is Required For the Developmenmentioning
confidence: 98%
“…It has been shown that neuropeptides such as NGF and kiss act as regulators of reproductive functions and can influence both the neuronal cell function (at the level of the central nervous system and peripheral system) and the inflammatory response (Sato et al 2017, Minnone et al 2017. Most inflammatory cells produce NGF and express TrkA.…”
Section: Figurementioning
confidence: 99%
“…Although the immunomodulatory effects of kiss have not been fully explored yet, it has been reported that the levels of this peptide in plasma rise abruptly during normal pregnancy and have direct effects on the regulatory subpopulations of T lymphocytes (Gorbunova & Shirshev 2016). On the other hand, it has been demonstrated that Kiss mRNA expression is increased by TNFα, IL-6, MCP-1 and VCAM-1 in human endothelial cells, and thus, accelerates atherogenesis by enhancing the inflammatory responses (Sato et al 2017). PCOS is associated with chronic low-grade inflammation and predisposition to hemostatic and atherosclerotic complications (Carvalho et al 2017), accompanied by high plasma levels of kiss (Chen et al 2010).…”
Section: Journal Of Endocrinologymentioning
confidence: 99%